2018
DOI: 10.1128/iai.00532-18
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Blocks Intracellular Interleukin-17 Signaling in Macrophages

Abstract: is an obligate intracellular bacterium and the etiological agent of Q fever. Successful host cell infection requires the type IVB secretion system (T4BSS), which translocates bacterial effector proteins across the vacuole membrane into the host cytoplasm, where they manipulate a variety of cell processes. To identify host cell targets of T4BSS effector proteins, we determined the transcriptome of murine alveolar macrophages infected with a T4BSS effector mutant. We identified a set of inflammatory genes that a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 87 publications
1
29
2
Order By: Relevance
“…To determine whether desipramine’s action on the pathogen was bacteriostatic or bactericidal, C. burnetii was allowed to infect HeLa cells and MH-S murine alveolar macrophages treated with desipramine or DMSO. Cells were harvested every 48 h to determine the number of viable bacteria using a colony-forming unit (CFU) assay ( Clemente et al, 2018 ). In control HeLa cells, a fourfold increase in bacterial load was observed, whereas the number of viable C. burnetii decreased over time in desipramine-treated cells ( Fig 6C ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether desipramine’s action on the pathogen was bacteriostatic or bactericidal, C. burnetii was allowed to infect HeLa cells and MH-S murine alveolar macrophages treated with desipramine or DMSO. Cells were harvested every 48 h to determine the number of viable bacteria using a colony-forming unit (CFU) assay ( Clemente et al, 2018 ). In control HeLa cells, a fourfold increase in bacterial load was observed, whereas the number of viable C. burnetii decreased over time in desipramine-treated cells ( Fig 6C ).…”
Section: Resultsmentioning
confidence: 99%
“…For C. burnetii infections, MH-S or HeLa cells were treated for 1 h with desipramine or DMSO and infected as previously described with mCherry-expressing small cell variants for 1 h ( Mulye et al, 2017 ; Clemente et al, 2018 ). Infection conditions were optimized for both cell type and vessel for less than one internalized bacterium per cell.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that certain pathogens actively interfere with the host IL-17 pathway. The mucosal pathogen Candida albicans inhibits IL-17 production in human hosts, which is the primary pathway for elimination of the fungus [ 115 ], and the intracellular bacteria Coxiella burnetii blocks IL-17 signaling in human macrophages [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…In BD activation of neutrophils and NLRP3 inflammasome (nucleotide-binding domain, leucine-rich containing family, pyrin domain-containing 3) is seen [ 41 , 42 ]. Nevertheless, C. Burnetii inhibits the NLRP3 inflammasome and also IL-17, important in neutrophil recruitment in BD [ 40 , 43 , 44 , 45 ]. Of interest, a similar tolerance induction using a recombinant Cholera toxin B subunit (conjugated with a peptide derived from the HSP protein 60) was therapeutically tried in BD uveitis [ 46 ].…”
Section: Discussionmentioning
confidence: 99%